The Use of the Total Physical Response Method in Arabic Language Lessons for Increase Mastery Vocabulary and Skills Speak Student - Insan Tamami, Fazri Nur (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
Purpose - The purpose of this research is to determine the vocabulary mastery and speaking skills in Arabic of students at Madrasah Tsanawiyah Persis 3 Pameungpeuk in the subject of Arabic before and after the implementation of the Total Physical Response method.Design/Methodology/Approach - The method employed in this research is a Quasi-Experiment with a pre-test and post-test design model in the experimental and control classes. The data collected for this study is both qualitative, examining the conditions of the location, and quantitative, focusing on calculations. Data collection techniques involve a combination of observation, interviews, testing, research, and literature review.Findings - Based on the research findings obtained in this study, it is evident that the vocabulary mastery and speaking skills in Arabic of students at Madrasah Tsanawiyah Persis 3 Pameungpeuk in the subject of Arabic before using the Total Physical Response method yielded a vocabulary score of 41 within the interpretation range of 0-49, indicating a low level, and a score of 54 in Arabic speaking skills within the interpretation range of 41-60, indicating a moderate level. Following the implementation of the Total Physical Response method, the post-test results yielded a vocabulary score of 54 within the interpretation range of 41-60, indicating a moderate level, and a score of 66 in Arabic speaking skills within the interpretation range of 61 -80, indicating a good level. Furthermore, the N-Gen testing resulted in a score of 4%, implying that the use of the Total Physical Response method in the subject of Arabic has a significant impact on student scores at a moderate level.Research Limitations/Implications - The issue in this research is confined by directing the study's focus on the influence of using the Total Physical Response method in improving vocabulary mastery and speaking skills in Arabic in the subject of Arabic among students of Madrasah Tsanawiyah Persis 3 Pameungpeuk .